2015
DOI: 10.1016/j.molmed.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Seeing through VEGF: innate and adaptive immunity in pathological angiogenesis in the eye

Abstract: The central role of VEGF signaling in regulating normal vascular development and pathological angiogenesis has been documented in multiple studies. Ocular anti-VEGF therapy is highly effective for treating a subset of patients with blinding eye disorders such as diabetic retinopathy and neovascular age-related macular degeneration (AMD). However, chronic VEGF suppression can lead to adverse effects associated with poor visual outcomes due to the loss of pro-survival and neurotrophic capacities of VEGF. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 98 publications
(96 reference statements)
3
94
0
1
Order By: Relevance
“…The change of immune response in the eye would affect its normal immune privileged state. 25,26 Based on the abovementioned evidence, it is not a surprise that lncRNA-related mRNAs are potentially involved in the regulation of CN.…”
Section: Discussionmentioning
confidence: 99%
“…The change of immune response in the eye would affect its normal immune privileged state. 25,26 Based on the abovementioned evidence, it is not a surprise that lncRNA-related mRNAs are potentially involved in the regulation of CN.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is well demonstrated that VEGF has a central role in the pathogenesis of wet age-related macular degeneration [45]. Increased VEGF production due to many factors such as the oxidative cell stress resulted in increased vascular permeability and neovascularization [46].…”
Section: Resultsmentioning
confidence: 99%
“…Kurihara et al [51,52] in the experimental study revealed an essential role of VEGF-A in regulating choroid vasculature and cone photoreceptors, responsible for central and color vision and evidenced that VEGF inhibition causes damage and loss of endothelial cells of the choriocapillaries and severe vision loss secondary to cone cell death in mice. Sene et al [53] also emphasized the critical role of chronic VEGF suppression as a cause of the loss of prosurvival and neurotrophic capacities of VEGF ending by vision loss. Multiple experimental studies were conducted on rat [54] , rabbit [55] and primate eye [56] to evaluate bevacizumab impact on choriocapillaris.…”
Section: Impact On Photoreceptors and Choriocapillarismentioning
confidence: 99%